PROBLEMS OF PARENTS IN GUIDING CHILDREN TO INCREASE AWARENESS OF PRAYING IN KLAMBIR V KEBUN VILLAGE, DELI SERDANG REGENCY - Agustia, Nanda Rahayu; Batu Bara, Fitri Amaliyah; Nofianti, Rita (Proceeding International Seminar of Islamic Studies, 2023)
Childhood is the most appropriate opportunity to educate various religious behaviors, including prayer education if the right methods and approaches are applied. Both parents are required to implement the commandments of Allah and the Sunnah of the Prophet as behavior and practice and continue to add to these sunnah practices as much as possible, because children will continue to supervise and imitate at all times. The child's ability to accept consciously or unconsciously is very high, beyond what we think, because we usually only see him as a small creature who does not understand and is not yet conscious. However, the reality is that awareness in carrying out prayers as a Muslim obligation is still very minimal among teenagers, especially rejama in Klambir V Kebun. This is problematic for parents to guide their children in increasing awareness of praying. To answer these problems, researchers are interested in conducting deeper research related to parental problems in guiding children to increase awareness of praying in Klambir V Village Kebun Deli Serdang. The results of the study: that there are several problems of parents in guiding children to increase awareness of worship in children in Klambir V Kebun village, namely: First) Electronic media such as TV, gadgets and others have a considerable share in association and examples of daily life. Many children neglect their prayers because of the preoccupation of watching TV and playing smartphones which are dominated by online game play. Second) Lack of parental attention, Parents who tend to be busy in their work affairs sometimes become less attentive to the condition of their children, the majority of parents are busy working from morning to evening, this causes the child to receive less supervision and attention. So if the child does not perform prayer, the parent will not know it. Third) Environment, children's play environment makes children lazy to perform prayers both at home and in the mosque because the majority of children are more interested in playing cellphones.